Insights into the oxygen vacancy filling mechanism in CuO/CeO2 catalysts: A key step toward high selectivity in preferential CO oxidation - Garcia Melchor, Max (My University, 2020)
The preferential CO oxidation (CO-PROX) reaction is paramount for the purification of reformate H2-rich streams, where CuO/CeO2 catalysts show promising opportunities. This work sheds light on the lattice oxygen recovery mechanism on CuO/CeO2 catalysts during CO-PROX reaction, which is critical to guarantee both good activity and selectivity, but that is yet to be well understood. Particularly, in situ Raman spectroscopy reveals that oxygen vacancies in the ceria lattice do not form in significant amounts until advanced reaction degrees, whereas pulse O2 isotopic tests confirm the involvement of catalyst oxygen in the CO and H2 oxidation processes occurring at all stages of the CO-PROX reaction (Mars–van Krevelen). Further mechanistic insights are provided by operando near-ambient pressure X-ray photoelectron spectroscopy (NAP–XPS) and near edge X-ray absorption fine structure (NEXAFS) experiments, which prove the gradual CuO reduction and steady oxidized state of Ce ions until the very surface reduction of CeO2 at the point of selectivity loss. Experiments are complemented by density functional theory (DFT) calculations, which reveal a more facile oxygen refill according to the trend CuO > CeO2 > Cu2O. Overall, this work concludes that the oxygen recovery mechanism in CO-PROX switches from a direct mechanism, wherein oxygen restores vacancy sites in the partially reduced CuO particles, to a synergistic mechanism with the participation of ceria once CuxO particles reach a critical reduction state. This mechanistic switch ultimately results in a decrease in CO conversion in favor of the undesired H2 oxidation, which opens-up future research on potential strategies to improve oxygen recovery.
PUBLISHED
Keywords: CO-PROX reaction; Ceria; Copper; Operando NAP−XPS; DFT calculations; Oxygen vacancies; Reaction mechanism; Nanoscience & Materials